NiII36‐Containing 54‐Tungsto‐6‐Silicate: Synthesis, Structure, Magnetic and Electrochemical Studies. Issue 61 (22nd September 2021) - Goura, Joydeb; Bassil, Bassem S.; Ma, Xiang; Rajan, Ananthu; Moreno‐Pineda, Eufemio; Schnack, Jürgen; Ibrahim, Masooma; Powell, Annie K.; Ruben, Mario; Wang, Jingjing; Ruhlmann, Laurent; Kortz, Ulrich
Abstract: The 36‐Ni II ‐containing 54‐tungsto‐6‐silicate, [Ni36 (OH)18 (H2 O)36 (SiW9 O34 )6 ] 6− (Ni36 ) was synthesized by a simple one‐pot reaction of the Ni2 ‐pivalate complex [Ni2 ( μ ‐OH2 )(O2 CCMe3 )4 (HO2 CCMe3 )4 ] with the trilacunary [SiW9 O34 ] 10− polyanion precursor in water and structurally characterized by a multitude of physicochemical techniques including single‐crystal XRD, FTIR, TGA, elemental analysis, magnetic and electrochemical studies. Polyanion Ni36 comprises six equivalent Ni II 6 SiW9 units which are linked by Ni−O−W bridges forming a macrocyclic assembly. Magnetic studies demonstrate that the Ni6 building blocks in Ni36 remain magnetically intact while forming a hexagonal ring with antiferromagnetic exchange interactions between adjacent Ni6 units. Electrochemical studies indicate that the first reduction is reversible and associated with the W VI/V couple, whereas the second reduction is irreversible attributed to the Ni II/0 couple. Abstract : The 36‐Ni II ‐containing 54‐tungsto‐6‐silicate, [Ni36 (OH)18 (H2 O)36 (SiW9 O34 )6 ] 6− (Ni36 ) was discovered and shown to contain more nickel centers than any other polyoxometalate (POMs) known to date. Polyanion Ni36 comprises six equivalent Ni II 6 SiW9 units which are linked by Ni−O−W bridges forming a macrocyclic assembly. Magnetic studies indicate antiferromagnetic communication between the six Ni6 subunits. Electrochemical studies indicate that the first reduction is reversible and associated to the W VI/V couple while the second reduction is irreversible and associated to the Ni II/0 couple.